The Prevalence of Oral Anomalies Among Healthy Newborns at a Gynecological Obstetric Hospital in Quito, Ecuador: An Observational, Cross-Sectional Study - Eleonor Vélez-León; Emilia Guerrero; Mauricio Orlando Carrillo; Marina Cabrera; Gustavo Tello; Patricia Pinos (Dentistry Journal)
Objectives: Early observations often fail to detect anomalies that may impact the health and quality of life of newborns. This study aimed to determine the prevalence of oral anomalies in newborns and explore their possible associations with sociodemographic factors. Methods: A cross-sectional study was conducted in Quito, Ecuador, analyzing a sample of 241 newborns. The presence of oral anomalies was recorded, and their association with sex, birth weight, maternal age, and gestational factors was evaluated. Results: The prevalence of oral anomalies was 72.3%, with Epstein’s pearls being the most common (50%). Other findings included Bohn’s nodules and dental lamina cysts, while no cases of natal teeth or congenital epulis were observed. Ankyloglossia was identified in 1.36% of newborns. No significant correlations were found between the presence of oral anomalies and sex, birth weight, maternal age, or gestational factors. Conclusions: The high prevalence (72.3%) of oral anomalies in the studied newborns underscores the importance of early detection and management. Epstein’s pearls were the most frequent anomaly, followed by Bohn’s nodules, dental lamina cysts, and ankyloglossia, while no cases of natal teeth or congenital epulis were identified. No statistically significant associations were found with sex, birth weight, maternal age, or pregnancy complications. These findings emphasize the need for early pediatric dental assessment and an interdisciplinary approach to ensure proper neonatal oral health. Further research is recommended to explore potential causes and interventions to optimize oral health from birth.